SEGREGASI DAN FENOTIPE TANAMAN LABU MADU (Cucurbita moschata) KETURUNAN KEDUA (F2) DALAM RANGKA MENGEMBANGKAN VARIETAS UNGGUL - Endang Sri Wahyuni (Pendidikan Biologi,Universitas Islam Jember, 2022)
The research, which aims to determine the segregation event in the second generation (F2) of honey gourd and the physical form (phenotype) formed, has been carried out from July to November 2021 at the Hydroponic Farm Greenhouse Pondok Bedadung Indah Jember. This research is without a method, but only planting seeds from F1 fruit planted in three places, namely NFT installation, polybag, and soil. Observations were made by weighing the fruit and looking at the physical form (phenotype) of the F2 pumpkin that was formed. The results showed that the shifts collected in F1 were 100% of uniform descent. After planting, segregation occurs and produces six phenotypes. Keywords: F2 phenotype, honey gourd, segregation.